Strategies for enhancing the quality of virtual education: perspectives of medical sciences faculty and students - a qualitative study - Maryam Saeedi; Marzieh Panahi (BMC Medical Education)
Abstract Background Virtual education has gained prominence in medical sciences, introducing new challenges in student training. It is therefore essential to identify strategies ensuring virtual education effectively equips medical students with requisite knowledge and skills. This study aimed to explore strategies for improving virtual education quality from the perspectives of medical sciences faculty and students. Methods This qualitative study employed conventional content analysis. Participants included 11 faculty members and 54 medical sciences students selected through purposive sampling. Data were collected via semi-structured individual and focus group interviews and analyzed using the Graneheim and Lundman method. Results The findings revealed two main categories: instructor-related strategies, including regular and scheduled teaching, engaging content design, alignment with in-person learning, effective virtual assessment, standardized assignments, active student engagement, and constructive interaction with students; and managerial/organizational strategies, including monitoring faculty teaching quality, empowering faculty members, supporting low-income students, and improving infrastructure. Conclusion Enhancing virtual education quality requires a multifaceted approach addressing both instructor-related and organizational dimensions. Implementing these strategies can foster more effective and inclusive virtual learning environments in medical education.